Increased level and interferon-γ production of circulating natural killer cells in patients with scrub typhus. - Seung-Ji Kang; Hye-Mi Jin; Young-Nan Cho; Seong Eun Kim; Uh Jin Kim; Kyung-Hwa Park; Hee-Chang Jang; Sook-In Jung; Seung-Jung Kee; Yong-Wook Park (Public Library of Science (PLoS), 2017)
Natural killer (NK) cells are essential immune cells against several pathogens. Not much is known regarding the roll of NK cells in Orientia tsutsugamushi infection. Thus, this study aims to determine the level, function, and clinical relevance of NK cells in patients with scrub typhus.This study enrolled fifty-six scrub typhus patients and 56 health controls (HCs). The patients were divided into subgroups according to their disease severity. A flow cytometry measured NK cell level and function in peripheral blood. Circulating NK cell levels and CD69 expressions were significantly increased in scrub typhus patients. Increased NK cell levels reflected disease severity. In scrub typhus patients, tests showed their NK cells produced higher amounts of interferon (IFN)-γ after stimulation with interleukin (IL)-12 and IL-18 relative to those of HCs. Meanwhile, between scrub typhus patients and HCs, the cytotoxicity and degranulation of NK cells against K562 were comparable. CD69 expressions were recovered to the normal levels in the remission phase.This study shows that circulating NK cells are activated and numerically increased, and they produced more IFN-γ in scrub typhus patients.